Public Infrastructure and Economic Development: Evidence from Postal Systems – Reproduction Report on Rogowski et al. (2022) - Florian Neubauer; Julian Rose; Jörg Ankel-Peters (Institute for Replication (I4R), 2023)
Rogowski et al. (2022) use secondary data to study the impact of historic postal infrastructure on economic development, both cross-country and within the US. Their results suggest a large positive effect of post offices on economic development that is robust across various sensitivity checks. We successfully computationally reproduce all results. In a robustness assessment, we find the results to be robust to simple changes in the analysis but observe some sensitivity to accounting for spatial trends in the cross-country analysis. Additionally, we correct a coding inconsistency, showing that in the corrected version, one main robustness check for the US-analysis is no longer supporting the result. Despite this, we find the results to be overall robust given the numerous analyses and robustness checks in the original paper.
Keywords: 330